DAMPAK SISTEM PRIMOGENITURE PADA MASYARAKAT INGGRIS ABAD KE-18 DALAM NOVEL PRIDE AND PREJUDICE KARYA JANE AUSTEN - Yulistiyanti Yulistiyanti (Dinamika Bahasa dan Budaya, 2010)
Literary works reflect the social life which the author lives in. It gives the reciprocal  effect between society and the works. Although, not all life is depicted in the works, it potrays part of human life in works. One of the example is Jane Austen’s Pride and Prejudice. This novel depicts the social condition of England in 18th century. Moreover, it reveals the women’s characteristics at that time. The characteristics of women in 18th century is materialistic. It is caused by the inheritance system, primogeniture which disallowed second son and daughter to inherit. It gives big impact to women and social condition. They could not fulfill their need, so they want to get partner who could give them anything, love and money. Assimilation happens in this era because of primogeniture.   Keyword: England, women, 18th century, materialistic, primogeniture